A review on numerical modeling for magnetic nanoparticle hyperthermia: Progress and challenges. (July 2020) - Raouf, Izaz; Khalid, Salman; Khan, Asif; Lee, Jaehun; Kim, Heung Soo; Kim, Min-Ho
Abstract: Recent progress in nanotechnology has advanced the development of magnetic nanoparticle (MNP) hyperthermia as a potential therapeutic platform for treating diseases. Due to the challenges in reliably predicting the spatiotemporal distribution of temperature in the living tissue during the therapy of MNP hyperthermia, critical for ensuring the safety as well as efficacy of the therapy, the development of effective and reliable numerical models is warranted. This article provides a comprehensive review on the various mathematical methods for determining specific loss power (SLP), a parameter used to quantify the heat generation capability of MNPs, as well as bio-heat models for predicting heat transfer phenomena and temperature distribution in living tissue upon the application of MNP hyperthermia. This article also discusses potential applications of the bio-heat models of MNP hyperthermia for therapeutic purposes, particularly for cancer treatment, along with their limitations that could be overcome. Graphical abstract: Image 1 Highlights: Mathematical models of MNP (Magnetic nanoparticles) hyperthermia are reviewed. Various methods are discussed for evaluating the SLP (Specific Loss Power). Different factors that optimizing the SLP are reviewed for hyperthermia applications. Bio-heat models and their applications are appraised for cancerous tumors. Limitations and challenges for the modeling of hyperthermia are addressed.